2017
DOI: 10.15804/tner.2017.50.4.14
|View full text |Cite
|
Sign up to set email alerts
|

The Use of E-learning Resources by Academic Teachers – a Polish-Czech Comparative Study

Abstract: The article is a result of the collaboration between Polish and Czech scientists who explore the issues of applying resources from the e-learning environment by academic teachers. The presented study was conducted in 2015-2016, within the project IRNet-International research network for study and development of new tools and methods for advanced pedagogical science in the field of ICT instruments, e-learning and intercultural competences. The research was aimed at learning academic teachers' opinions on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results of the fourth study, directed at academic staff, showed that university teachers use a number of electronic instruments for the implementation of education, the management of students' self-study and study communication to enhance the elements of online distance learning. Its actual choice or potential preferences are not much influenced by teachers' age but rather by their user level of ICT competence and in some cases also by their involvement in social networks (Ogrodzka-Mazur, Szafrańska, Malach & Chmura, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the fourth study, directed at academic staff, showed that university teachers use a number of electronic instruments for the implementation of education, the management of students' self-study and study communication to enhance the elements of online distance learning. Its actual choice or potential preferences are not much influenced by teachers' age but rather by their user level of ICT competence and in some cases also by their involvement in social networks (Ogrodzka-Mazur, Szafrańska, Malach & Chmura, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It further increases the learning-oriented motivation of students, may increase the active participation of students and positively influence the process of learning in the branch of tertiary education (Tan et al, 2018). E-learning, considering its sophistication and complexity, represents an educational platform suitable for the university environment (Ogrodzka-Mazur et al, 2017). It allows for the development of higher cognitive processes such as analysis, evaluation and creativity, which require an extensive interaction and collaboration between students and facilitators (Lau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%